2007
DOI: 10.1016/j.ygeno.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome profiling of region-specific vulnerability to oxidative stress in the hippocampus

Abstract: Neurons in the hippocampal CA1 region are particularly sensitive to oxidative stress (OS), whereas those in CA3 are resistant. To uncover mechanisms for selective CA1 vulnerability to OS, we treated organotypic hippocampal slices with duroquinone and compared transcriptional profiles of CA1 vs CA3 cells at various intervals. Gene Ontology and Biological Pathway analyses of differentially expressed genes showed that at all time points, CA1 had higher transcriptional activity for stress/inflammatory response, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 66 publications
0
58
0
2
Order By: Relevance
“…4F–J). Previous literatures reported that releasing progerin from the nuclear membrane by farnesyltransferase inhibitor treatment partially rescued the gene expression and morphological defects in HGPS cells (Capell et al ., 2005, 2008; Capell & Collins, 2006; Gelb et al ., 2006; Cao et al ., 2007; Wang et al ., 2007; Marji et al ., 2010). Indeed, we find that not only the nuclear morphology but also the chromatin organization and gene expression are improved in the MB‐treated HGPS nucleus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4F–J). Previous literatures reported that releasing progerin from the nuclear membrane by farnesyltransferase inhibitor treatment partially rescued the gene expression and morphological defects in HGPS cells (Capell et al ., 2005, 2008; Capell & Collins, 2006; Gelb et al ., 2006; Cao et al ., 2007; Wang et al ., 2007; Marji et al ., 2010). Indeed, we find that not only the nuclear morphology but also the chromatin organization and gene expression are improved in the MB‐treated HGPS nucleus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This observation correlates with the finding that cyclooxygenase‐2, which is up‐regulated at sites of inflammation, is also primarily up‐regulated in these neurons (29). Lcn2 mRNA expression was also found to be up‐regulated in area CA1 of the hippocampus in rat after oxidative stress in vivo (54), indicating that Lcn2 is up‐regulated in hippocampus tissue during neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for studying metabolite changes in two brain regions was based on our past observations that neurons in adjoining regions of the brain may differ very significantly in terms of gene expression patterns and in their vulnerability to metabolic and oxidative stress, including the stress brought about by the aging process [38, 39, 51, 5457]. Furthermore, it has previously been shown that the levels of Glu, Gln, GABA and Asp may vary by a factor of five and up to a factor of 21 in different regions of rat brains, and that the effects of aging on the levels of these amino acids are not identical across various rat [58] or mouse brain regions [59].…”
Section: Discussionmentioning
confidence: 99%